The therapeutic potential of Gua Sha on fascia: evidence and possible mechanisms - Wang, Beibei; Chen, Hongxiu; Eungpinichpong, Wichai (International Journal of Public Health Science (IJPHS), 2025)
In recent years, the effects of Gua Sha on fascia have gradually attracted attention. This review evaluates the effects of Gua Sha on fascia and its underlying mechanisms. We searched major academic databases for relevant studies using the keywords "Gua Sha or scraping," "fascia or pain or inflammation," and "randomized controlled trial (RCT)." Only RCTs published in English were included. Two independent reviewers screened and assessed the methodological quality of the studies using the PEDro scoring scale. After applying the inclusion criteria, nine studies involving 436 participants were included in the final analysis. The methodological quality of the included studies varied, with PEDro scores ranging from 6 to 9. Research results suggest that Gua Sha may help relieve pain, reduce fascial inflammation, and increase flexibility. Potential mechanisms include improved blood and lymph circulation, neuromodulation, and mechanical stimulation. These results highlight the potential of Gua Sha as an alternative treatment for fascia-related problems. Further studies are needed to consolidate these findings and elucidate the underlying mechanisms.